2016
DOI: 10.1128/iai.00345-16
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba castellanii Genotype T4 Stimulates the Production of Interleukin-10 as Well as Proinflammatory Cytokines in THP-1 Cells, Human Peripheral Blood Mononuclear Cells, and Human Monocyte-Derived Macrophages

Abstract: Free-living amoebae of the genus Acanthamoeba can cause severe and chronic infections in humans, mainly localized in immune privileged sites, such as the brain and the eye. Monocytes/macrophages are thought to be involved in Acanthamoeba infections, but little is known about how these facultative parasites influence their functions. The aim of this work was to investigate the effects of Acanthamoeba on human monocytes/macrophages during the early phase of infection. Here, THP-1 cells, primary human monocytes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…IL‐1β appears whenever cellular activation against a pathogen occurs in a host tissue. It is secreted in reaction to PAMPs, specifically to certain lipopolysaccharides recognized by TLR‐4 . Thus, inflammatory cells positive to IL‐1β indicate the presence of a pathogen or of cell damage in host tissues .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL‐1β appears whenever cellular activation against a pathogen occurs in a host tissue. It is secreted in reaction to PAMPs, specifically to certain lipopolysaccharides recognized by TLR‐4 . Thus, inflammatory cells positive to IL‐1β indicate the presence of a pathogen or of cell damage in host tissues .…”
Section: Discussionmentioning
confidence: 99%
“…At 4 and 8 weeks, there were other cells positive to the same cytokine, including those of the outer part of the corneal epithelium. Mattana et al reported the secretion of IL‐10 by macrophages in vitro in response to contact with A castellanii . The anti‐inflammatory element during the inflammatory response of the host probably has the purpose of limiting damage caused by pro‐inflammatory molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy could be explained by differences between murine and human cells or the experimental techniques optimized for each cell type. This would include differences in the numbers of trophozoites used in the coincubation models, as well as the time of observations, each of which was optimized to allow coculture with minimal cell death but with a sufficient interaction to induce measurable levels of cytokines (30). In addition, we also investigated whether conditioned medium derived from Acanthamoeba cultures could mimic some of the effects observed on human cells (30,31), but we found conditioned medium to be less effective with murine cells.…”
Section: Discussionmentioning
confidence: 99%
“…This would include differences in the numbers of trophozoites used in the coincubation models, as well as the time of observations, each of which was optimized to allow coculture with minimal cell death but with a sufficient interaction to induce measurable levels of cytokines (30). In addition, we also investigated whether conditioned medium derived from Acanthamoeba cultures could mimic some of the effects observed on human cells (30,31), but we found conditioned medium to be less effective with murine cells. These differences could be species dependent or due to differences in culture conditions, including medium components, such as the concentration of heat-inactivated fetal bovine serum.…”
Section: Discussionmentioning
confidence: 99%